2012
DOI: 10.1186/1472-6882-12-226
|View full text |Cite
|
Sign up to set email alerts
|

Wound repair and anti-inflammatory potential of Lonicera japonica in excision wound-induced rats

Abstract: BackgroundLonicera japonica Thunb. (Caprifoliaceae), a widely used traditional Chinese medicinal plant, is used to treat some infectious diseases and it may have uses as a healthy food and applications in cosmetics and as an ornamental groundcover. The ethanol extract of the flowering aerial parts of L. japonica (LJEE) was investigated for its healing efficiency in a rat excision wound model.MethodsExcision wounds were inflicted upon three groups of eight rats each. Healing was assessed by the rate of wound co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
47
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(49 citation statements)
references
References 29 publications
2
47
0
Order By: Relevance
“…20,21 Recently, it was reported that LJ has anti-inflammatory properties in animal models of osteoarthritis and excision wounding. 22,23 For example, in these animal models, LJ was found to suppress a number of inflammation-related phenomena and the amount of cytokines produced, including TNF-a and IL-6. Moreover, LJ was shown to have anti-inflammatory effects in a carrageenaninduced paw edema inflammation model.…”
Section: Introduction Mmentioning
confidence: 99%
“…20,21 Recently, it was reported that LJ has anti-inflammatory properties in animal models of osteoarthritis and excision wounding. 22,23 For example, in these animal models, LJ was found to suppress a number of inflammation-related phenomena and the amount of cytokines produced, including TNF-a and IL-6. Moreover, LJ was shown to have anti-inflammatory effects in a carrageenaninduced paw edema inflammation model.…”
Section: Introduction Mmentioning
confidence: 99%
“…Non-significant difference in the hexosamine level of wound biopsy from animals in all the groups further suggest that the extract and the reference drug exerted comparable collagen stabilization and thus wound healing effect. Enhanced hydroxyproline and hexosamine synthesis provides strength to repaired tissue and stimulates healing (Chen et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The fact that the wound breaking strength of group I (20% MESDR) significantly increased when compared with group II and the control, suggest that 20% extract concentrations may have promoted collagen synthesis, fibroblast proliferation and neo-vascularization better than the 10% concentration and the reference drug. But the best method of assessing collagen turnover or synthesis is measuring the hydroxproline (the major amino acid component of collagen) and hexosamine level in wound biopsy (Chen et al, 2012). Increase in hydroxyproline content indicates increased collagen synthesis and invariably wound healing while increased hexosamine content reflects the stabilization of collagen molecules via enhanced electrostatic and ionic interactions (Ricard-Blum and Ruggiero, 2005; Chen et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…has been used for thousands of years as traditional Chinese medicine owing to its bacteriostasis (Tang et al, 2008), antitumor (Liu et al, 2012), antioxidant (Gong et al, 2006), anti-endotoxin (Yang et al, 2012), antiinflammatory (Kang et al, 2004;Chen et al, 2012), antiviral (Yan et al, 1998), proimmune (Cui, 2011), and blood sugar-lowering effects (Liang et al, 2011). In commercial production, many species from the family Caprifoliaceae, including Lonicera similis Hemsl., Lonicera macranthoides Hand.-Mazz., Lonicera acuminata Wall., and Lonicera hypoglauca Miq., have been applied as Lonicera japonica.…”
Section: Introductionmentioning
confidence: 99%